"You`ve got to be really careful": Concerns from coaches on applying female athlete physiology education in sport - Daniel, M. (International Journal of Sports Science and Coaching, 2026)
Female athletes are increasingly seeking knowledge and support from coaches regarding the menstrual cycle as it relates to health and performance in sport. Yet few coaches feel equipped to provide this support due to low levels of knowledge about female-specific physiology, communication barriers, and lack of access to female-specific health education. This study qualitatively examines how male and female coaches of female athletes aged 15 + responded to an online education series on supporting female athlete health and performance. Coaches were encouraged to actively apply their learning in their coaching by sharing supplemental handouts and discussing menstrual health with athletes. Coaches then shared their concerns and experiences through surveys (n = 21) and interviews (n = 5). Analysis revealed that: (1) coaches were surprised to learn that menstrual health and symptom management is a significant concern for female athletes, (2) coaches had concerns that discussing menstrual health might violate social norms, gender roles, and/or exceed the scope of their leadership responsibilities, and (3) coaches desire support in translating menstrual health learning into their work with female athletes. Additionally, female coaches (i.e., those with lived experience with the menstrual cycle) were more likely to implement menstrual health awareness in their coaching, as they were able to relate to female athletes` concerns and experiences with the menstrual cycle in sport. This study concluded that coaches` comfort in discussing menstrual health with athletes can be developed and that both male and female coaches need translational support to navigate the social stigma associated with the menstrual cycle.